Interleukin-5 (IL-5) Therapy Prevents Allograft Rejection by Promoting CD4+CD25+ Ts2 Regulatory Cells That Are Antigen-Specific and Express IL-5 Receptor - Hall, Bruce M.; Hall, Rachael M.; Tran, Giang T.; Robinson, Catherine M.; Wilcox, Paul L.; Rakesh, Prateek K.; Wang, Chuanmin; Sharland, Alexandra F.; Verma, Nirupama D.; Hodgkinson, Suzanne J. (Frontiers in Immunology, 2021)
Activation of naïve CD4+CD25+Foxp3+T regulatory cells (tTreg) by specific alloantigen and IL-4, not IL-2, induces Ts2 cells that express the IL-5 receptor (IL-5Ra). Ts2 cells are more potent than tTreg in suppressing specific alloimmune responses. We examined whether treatment with rIL-5 promoted Ts2 cells to reduce chronic rejection of Lewis heart allografts in F344 rats. Host CD4+CD25+T cells were assessed by FACS, in mixed lymphocyte culture and by RT-PCR. rIL-5 treatment given 7 days after transplantation reduced the severity of rejection and all grafts survived >60d whereas sham treated rats fully rejected their graft by day 31 (p<0.01). Treatment with anti-CD25 or anti-IL-4 monoclonal antibody abolished the benefits of treatment with rIL-5 and accelerated rejection. This is consistent with host CD25+T cells being induced to Ts2 cells that were promoted by rIL-5 treatment. After 10d treatment with rIL-5, hosts’ CD4+CD25+T cells expressed more Il5ra and responded to specific donor Lewis but not self. CD4+CD25+T cells from rIL-5 treated rats with allografts surviving >60 days proliferated to specific donor only when rIL-5 was present and did not proliferate to self or third party. These cells had more mRNA for Irf4 and Il5, which are molecules expressed by Th2-like Treg. IL-5 prevented chronic rejection by enhancing host CD25+Treg that had been activated by alloantigen and IL-4.